The Influence of Economic Value Added (EVA) and Market Value Added (MVA) on Stock Returns - Gilbert Rely (Jurnal Ekonomi, 2024)
This study investigates the impact of Economic Value Added (EVA) and Market Value Added (MVA) on stock returns of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange from 2019 to 2023. Using a quantitative approach with multiple regression analysis, the research reveals that EVA positively and significantly influences stock returns, with an EVA value of 5.299 and a significance level of 0.011. Conversely, MVA shows a negative and significant impact, with a recorded value of -3.471 and a significance level of 0.048, indicating that the company is failing to generate the expected added value for shareholders. The F test also demonstrates that EVA and MVA jointly have a significant effect on stock returns, with a significance value of 0.039, underscoring the need for effective management to create added value, attract investors, and improve stock performance.